Modal sosial dalam pengembangan potensi objek wisata di Pulau Abang Batam Kepulauan Riau - M Yusuf; Hesti Asriwandari; Siti Sofro Sidiq (EcoNews, 2022)
Initially, tourism was seen as an economic activity, and the main purpose of tourism development was to gain economic benefits, both for the community and the region/country. Tourism has a high impact on people's lives. So the importance of community readiness in tourism development. Knowledge about tourism is needed. Mentoring and also social capital of the community itself for good tourism development. The condition of tourism on Abang Island for six years of existence is still premature. The vacuum of tourism-aware groups makes tourism difficult to develop.The title of this research is social capital of tourism development in Abang Island, Batam, Riau Archipelago. The results of this study show and explain that the social capital of the community on Abang Island does not have the impetus for tourism development. The habit factor of the people on Abang Island can be a driving factor for social capital for tourism development. Position and role factors, education, social class and economic disparities as well as consumption patterns and personal values ​​can hinder social capital in tourism development. In the current conditions, competition for tourism managers is not only among the people who become managers but also competes with resorts on Abang Island. This makes managers implement active, passive and network strategies so that they can still be tourism managers on Abang Island.